Convergence and Characterization of Wavelets Associated with Dilation Matrix in Variable Spaces - Devendra Kumar (Journal of Mathematics)
We study the convergence of wavelet expansions associated with dilation matrix in the variable spaces using the approximate identity. Also, we obtain conditions for the wavelet characterizations of with respect to norm estimates. Moreover, the results of Izuki (2008) and Kumar (2009) have been extended.